Implikasi Eksekusi Kurator Atas Aset Debitor Pailit Yang Berada Di Luar Batas Yuridiksi Indonesia - Saija, Ronald; Nabila, Syadzwina Hindun; Panjaitan, Wijaya Natalia; Lenggono, Roy Prabowo (Balobe Law Journal, 2024)
Introduction: The development of an increasingly advanced economic system seems to have opened up opportunities for cooperation that can be built by entrepreneurs both at home and abroad. The business world is also conducted not only within one's own country, but the business world is now developing to establish business relationships with other countries in the world (transnational). In this way, the assets owned by debtors or creditors are not in their own country but are in other countries. Business relationships carried out between debtors and creditors do not always run smoothly, if these business relationships fail, it will happen that both debtor and creditor assets are located in several countries and this also results in multiple jurisdictions.Purposes of the Research: This research aims to analyze the implications of the curator's execution of assets of bankrupt debtors outside the jurisdiction of Indonesia.Methods of the Research: This research uses a normative juridical method with a statutory approach and a conceptual approach, and legal materials are analyzed using a deductive method.Results of the Research: That Law No. 37 of 2004 concerning Bankruptcy and PKPU does not regulate the authority of curators in executing bankruptcy cases outside the jurisdiction of Indonesia, especially those that conflict with the jurisdiction of other countries, so it is necessary to revise the Bankruptcy Law regarding Cross-Border Bankruptcy, especially in terms of supporting ease of doing business.